QUALITY OF INVESTMENT DECISION, BUSINESS RISK, EFFICIENCY AND PROFIT GROWTH - Axel Giovanni; Yacobo P. Sijabat; Heni Hirawati; Alifa Jauzaa (Jurnal Riset Bisnis dan Manajemen, 2022)
Earnings growth is an indicator that shows the company's capability to increase net profit in a certain period compared to the previous period. This study aims to provide empirical evidence regarding the role of investment decision quality, business risk, and efficiency on corporate earnings growth. The research population includes all companies in the property, real estate and building construction sectors. The research sample was 50 companies which were obtained through purposive sampling method. This research uses linear regression analysis method. The results provide evidence that the quality of investment decisions, business risk and efficiency have a significant role in the earnings growth of the company in the property, real estate and building construction sectors.